PENERAPAN MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN KESIAPAN DAN PRESTASI BELAJAR PADA MATA PELAJARAN IPA - Fenny Valensi (UNIB Press, 2023)
The research objective was to describe the application and effectiveness of the inquiry learning model in improving student learning readiness and science learning achievement in grade IV SD Negeri 3 Kaur. The approach in this study used a combination of Classroom Action Research (CAR) and quasi-experimental types. The research subjects were 23 students of class IVA, 23 students of IVB and 23 students of SD Negeri 3 Kaur. Methods of data collection using observation sheets and tests. Data analysis used mean analysis and t test. The results of the research in Cycle 1 PTK class showed that 15 students were in the unprepared category and 9 students had not yet completed their science learning achievement. In cycle 2 only 1 student was in the less prepared category and only 4 students had not yet completed science learning achievement. In cycle 3, none of the students were in the unprepared and incomplete category in science learning achievement. The results of the quasi-experimental research showed that there was a significant difference in the pretest and posttest scores of the experimental class, but there was no significant difference in the control class. The conclusion of this research is the application of the Inquiry learning model in a gradual manner and can improve learning readiness and achievement of science students in grade IV SD Negeri 3 Kaur